2011
DOI: 10.1039/c1em10470e
|View full text |Cite
|
Sign up to set email alerts
|

Long-range atmospheric transport of persistent organochlorinated compounds from south and mainland south-eastern Asia to a remote mountain site in south-western China

Abstract: A range of organochlorinated compounds have been consumed in China, India and the countries of mainland southeast Asia (MSA). Considering their persistence in the environment and ability in longrange atmospheric transport (LRAT), the potential outflow of these compounds from this region is therefore of great concern in the context of the global distribution of toxic chemicals. As part of a monitoring campaign aimed at investigating the LRAT of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In contrast to this, Li et al (2006) found the source of OCPs in Lhasa to be current use and local emission. Xu et al (2011) studied the transportation characteristics of OCPs and their potential sources at remote stations, such as Tengchong Mountain (TM) in the south-western part of China, and found elevated levels of HCHs and DDTs in the air. Potential source contribution function (PSCF) analysis suggests that high levels of OCPs at TM are mainly caused by LRAT from India and Southern China.…”
Section: The Role Of India In the Global Distribution Of Persistent Omentioning
confidence: 99%
“…In contrast to this, Li et al (2006) found the source of OCPs in Lhasa to be current use and local emission. Xu et al (2011) studied the transportation characteristics of OCPs and their potential sources at remote stations, such as Tengchong Mountain (TM) in the south-western part of China, and found elevated levels of HCHs and DDTs in the air. Potential source contribution function (PSCF) analysis suggests that high levels of OCPs at TM are mainly caused by LRAT from India and Southern China.…”
Section: The Role Of India In the Global Distribution Of Persistent Omentioning
confidence: 99%
“…Becker et al (2011) estimated that in the Arctic environment, air masses from temperate, subtropical, and tropical regions may contribute to the amount of endosulfan I in the ratio of 57:40:3, respectively, and of endosulfan II in the ratio of 66:33:1, respectively. For a remote mountain site in southwestern China, Xu et al (2011) found that HCH and DDT levels increased when air masses originated from India and Southeast Asia during the summer monsoon. Generally, the movement of air masses containing OCPs to Europe and the European Alps may occur during warmer seasons, when higher temperatures increase the mobility of semivolatile compounds.…”
Section: Geographic Originmentioning
confidence: 99%
“…Two types of sites have been the object of such analyses. The first comprises remote areas where measurements are scarce or are assumed to be clean (Xu et al 2011), and the second comprises areas that are especially polluted (Lv et al 2015).…”
Section: Introductionmentioning
confidence: 99%